E-261 An institutional experience adopting transradial cerebral angiography. (23rd July 2022) - Alwakeal, A; Abdalla, R; Nandoliya, K; Klein, J; Winterhalter, E; Kazanchi, R; Ansari, S; Cantrell, D; Shaibani, A; Jahromi, B; Potts, M
Abstract : Background: Transradial artery access in cerebral angiography has been widely adopted in cardiac angiography and is gaining popularity in cerebral angiography. We recently adopted this technique in our institutional cerebral angiography practice and sought to evaluate our experience. Method: We conducted a retrospective review of transradial diagnostic cerebral angiograms performed at our institution between 2020 and 2022 and compared procedural characteristics between transfemoral cerebral angiograms performed at our institution between June 2018 and 2022. Results: One hundred fifty-four transradial cerebral angiograms were identified and compared to 467 transfemoral cerebral angiograms. The mean ages of the transradial and transfemoral cohorts were 53.34 and 53.93, respectively. The mean fluoroscopy time in the transradial group was 24.9 ± 21.9 minutes compared to 22.7 ±39.5 minutes in the transfemoral group, while the mean radiation dose was 495.64 mGy and 549.04 mGy and for the radial and femoral groups, respectively. The mean recovery time for radial patients was 1 hour 42 minutes for radial patients and 2 hours 3 minutes for femoral patients. There were no significant differences between these procedural metrics. Conclusion: Transradial artery access for diagnostic cerebral angiography can be successfully adopted in a busy neurointerventional practice. Disclosures: A. Alwakeal: None. R. Abdalla: None. K. Nandoliya: None. J. Klein: None. E. Winterhalter: None. R. Kazanchi: None. S. Ansari: None. D. Cantrell: None. A. Shaibani: None. B. Jahromi: None. M. Potts: None.